Pacritinib versus best available therapy for the treatment of myelofibrosis irrespective of baseline cytopenias (PERSIST-1): an international, randomised, phase 3 trial. Issue 5 (May 2017) - Mesa, Ruben A; Vannucchi, Alessandro M; Mead, Adam; Egyed, Miklos; Szoke, Anita; Suvorov, Aleksandr; Jakucs, Janos; Perkins, Andrew; Prasad, Ritam; Mayer, Jiri; Demeter, Judit; Ganly, Peter; et al.
Summary: Background: Available therapies for myelofibrosis can exacerbate cytopenias and are not indicated for patients with severe thrombocytopenia. Pacritinib, which inhibits both JAK2 and FLT3, induced spleen responses with limited myelosuppression in phase 1/2 trials. We aimed to assess the efficacy and safety of pacritinib versus best available therapy in patients with myelofibrosis irrespective of baseline cytopenias. Methods: This international, multicentre, randomised, phase 3 trial (PERSIST-1) was done at 67 sites in 12 countries. Patients with higher-risk myelofibrosis (with no exclusions for baseline anaemia or thrombocytopenia) were randomly assigned (2:1) to receive oral pacritinib 400 mg once daily or best available therapy (BAT) excluding JAK2 inhibitors until disease progression or unacceptable toxicity. Randomisation was stratified by risk category, platelet count, and region. Treatment assignments were known to investigators, site personnel, patients, clinical monitors, and pharmacovigilance personnel. The primary endpoint was spleen volume reduction (SVR) of 35% or more from baseline to week 24 in the intention-to-treat population as assessed by blinded, centrally reviewed MRI or CT. We did safety analyses in all randomised patients who received either treatment. Here we present the final data. This trial is registered withClinicalTrials.gov, numberNCT01773187 . Findings: Between Jan 8, 2013, and Aug 1, 2014, 327 patients were randomly assigned to pacritinib (n=220) or BAT (n=107). Median follow-up was 23·2 months (IQR 14·8–28·7). At week 24, the primary endpoint of SVR of 35% or more was achieved by 42 (19%) patients in the pacritinib group versus five (5%) patients in the BAT group (p=0·0003). 90 patients in the BAT group crossed over to receive pacritinib at a median of 6·3 months (IQR 5·8–6·7). The most common grade 3–4 adverse events through week 24 were anaemia (n=37 [17%]), thrombocytopenia (n=26 [12%]), and diarrhoea (n=11 [5%]) in the pacritinib group, and anaemia (n=16 [15%]), thrombocytopenia (n=12 [11%]), dyspnoea (n=3 [3%]), and hypotension (n=3 [3%]) in the BAT group. The most common serious adverse events that occurred through week 24 were anaemia (10 [5%]), cardiac failure (5 [2%]), pyrexia (4 [2%]), and pneumonia (4 [2%]) with pacritinib, and anaemia (5 [5%]), sepsis (2 [2%]), and dyspnoea (2 [2%]) with BAT. Deaths due to adverse events were observed in 27 (12%) patients in the pacritinib group and 14 (13%) patients in the BAT group throughout the duration of the study. Interpretation: Pacritinib therapy was well tolerated and induced significant and sustained SVR and symptom reduction, even in patients with severe baseline cytopenias. Pacritinib could be a treatment option for patients with myelofibrosis, including those with baseline cytopenias for whom options are particularly limited. Funding: CTI BioPharma Corp.